2017
DOI: 10.29309/tpmj/2017.24.08.1006
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Artery Stenosis

Abstract: Objectives: The objective of this study is to determine the frequency of carotidartery atherosclerosis using color Doppler ultrasound in ischemic stroke patients. StudyDesign: Cross-sectional study. Period: July 2015 to June 2016. Setting: Khyber TeachingHospital, Peshawar. Method: Doppler ultrasonography was done to assess carotid artery statusin patients diagnosed with cerebral infarction. Results: Data comprised of 174 ischemic strokepatients between ages 37-95 years. 111 were males whereas 63 were males. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Our study showed a significantly higher prevalence in men (57.1%) than in women (42.9%) coincides with other studies 20, 24, 25. In our study majority of the plaques were located in the common carotid artery of the left carotid artery similar to Kwon TG et al andKhattak et al 19,26 In contrast to Gul Z et al, and Thatipamula MK et al, showed a majority of plaques were located in the left carotid bulb 25.8% 27.…”
supporting
confidence: 86%
“…Our study showed a significantly higher prevalence in men (57.1%) than in women (42.9%) coincides with other studies 20, 24, 25. In our study majority of the plaques were located in the common carotid artery of the left carotid artery similar to Kwon TG et al andKhattak et al 19,26 In contrast to Gul Z et al, and Thatipamula MK et al, showed a majority of plaques were located in the left carotid bulb 25.8% 27.…”
supporting
confidence: 86%